Synergistic effect of carbon fiber and graphite on reducing thermal resistance of thermal interface materials. (18th August 2021) - Li, Maohua; Li, Linhong; Hou, Xiao; Qin, Yue; Song, Guichen; Wei, Xianzhe; Kong, Xiangdong; Zhang, Zhenbang; Do, Hainam; Greer, James C.; Han, Fei; Cai, Tao; et al.
Abstract: Thermal interface materials (TIM) have become a leading solution to achieve lower operating temperature in electronic devices. To improve thermal conductivity and to simultaneously reduce thermal resistance, this work investigates the thermal properties for interface materials with carbon fiber and graphite. When the ratio between carbon fiber to graphite is 1:1, the thermal resistance can be reduced to 1.8 × 10 −4  K m 2  W −1 at 30 psi, although the bulk thermal conductivity is lowered from 34 to 19 W m −1  K −1 . The synergistic effect between carbon fiber and graphite is investigated. Surface roughness of TIMs was measured and two different types of thermal conductivity measurement were applied to demonstrate that graphite makes a contribution to bulk thermal conductivity where a CF played an important role for smoothing the surface, thereby lowering the thermal resistance. In real applications, the hybrid filler is shown to perform better in enhancing the heat conduction for electrical packaging. Graphical abstract: Image 1 Highlights: Construction of thermal interface material with low thermal resistance and high thermal conductivity. Investigate the synergism of carbon fiber and graphite which induces reduction of thermal resistance. Enhance heat transfer by strengthening the coupling between filler and matrix. Provide a low-cost and practical method to produce TIM with high thermal conductivity.